2017
DOI: 10.1155/2017/5792925
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Tenofovir Disoproxil Fumarate Based Regimen as Compared to Zidovudine Based Regimens: A Systematic Review and Meta-Analysis

Abstract: Background Although tenofovir (TDF)/emtricitabine (FTC)/efavirenz (EFV) and zidovudine (ZDV)/lamivudine (3TC)/efavirenz (EFV) are used as preferred first line regimen, their head-to-head comparison in terms of their efficacy and tolerability was limited. This review aimed to synthesize the best available evidence on the comparative efficacy and tolerability of the two regimens. Methods Seven sites and databases in addition to Google search until August 20, 2016, were searched. Only randomized clinical trials c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 11 publications
3
19
1
Order By: Relevance
“…This might be because AZT-3TC-NVP is taken twice per day (drug burden) that results in the patient not taking the drug appropriately and end up with LTFU and also TDF-3TC-EFV is fixed-dose combinations of ART agents which helps to reduce dosing complexity [45]. Tenofovir regimen is claimed to have a better safety profile, even though it may result renal toxicity, compared to zidovudine because of a reduced incidence of anemia and fat redistribution [46][47][48][49][50], so patients with AZT-3TC-NVP may have a loss of hope on the medication if they become ill due to anemia and other complications and finally may be lost from HIV care [32].…”
Section: Discussionmentioning
confidence: 99%
“…This might be because AZT-3TC-NVP is taken twice per day (drug burden) that results in the patient not taking the drug appropriately and end up with LTFU and also TDF-3TC-EFV is fixed-dose combinations of ART agents which helps to reduce dosing complexity [45]. Tenofovir regimen is claimed to have a better safety profile, even though it may result renal toxicity, compared to zidovudine because of a reduced incidence of anemia and fat redistribution [46][47][48][49][50], so patients with AZT-3TC-NVP may have a loss of hope on the medication if they become ill due to anemia and other complications and finally may be lost from HIV care [32].…”
Section: Discussionmentioning
confidence: 99%
“…Results from this study show that a tenofovir combination HAART (especially a combination with efavirenz) may have a slight edge over a zidovudine combination HAART. In a systematic review and meta-analysis, a tenofovir combination HAART showed superior viral load suppression, and was better tolerated by patients [ 24 ]. However, emtricitabine, instead of lamivudine was the supporting drug.…”
Section: Discussionmentioning
confidence: 99%
“…Zidovudine is an ARV which belongs to the class of nucleoside reverse transcriptase inhibitors (NRTIs). [3][4][5] However, both drugs are associated with side effects Both the regimens zidovudine and tenofovir are used as first line antiretroviral treatment (ART), although zidovudine is associated with side-effects such as chronic anemia, which are likely to affect patients' QoL (Quality of life). In case of Tenofovir it has a better safety profile compared to zidovudine, with the main side-effect being renal toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…6 According to some studies tenofovir is superior to zidovudine in terms of its safety profile because of a reduced incidence of anemia and fat redistribution. 4,[7][8][9] Some other studies revealed that Tenofovir had fewer side effects, but the range of side-effects studied was limited. 10 There are limited data comparing ZLN (Zidovudine+Lamivudine+Nevirapine) and TLE (Tenofovir+Lamivudine+Efavirenz).…”
Section: Introductionmentioning
confidence: 99%